Anatomy of the underground system in Vernonia grandiflora Less. and V. brevifolia Less. (Asteraceae) - Hayashi,Adriana Hissae (2007)
This work dealt with the anatomy of the underground system in Vernonia grandiflora Less. and V. brevifolia Less. (Vernonieae; Asteraceae), two perennial geophytes, to elucidate their ability to sprout in the Brazilian Cerrado conditions. V. grandiflora, a subshrubby species, possessed a thickened underground system constituted by a xylopodium and many tuberous roots. The xylopodium had stem and root structure and its buds were axillary or originated from the cortical parenchyma proliferation. The tuberous roots produced by this organ were adventitious and accumulated inulin-type fructans mainly in the cortical parenchyma. The thickened underground system of V. brevifolia, an herbaceous species, was a tuberous primary root whose buds originated from the proliferated pericycle. The occurrence of these bud-forming underground systems, which stored reserve compounds, enabled these plants to survive throughout unfavourable environmental conditions in the Cerrado, such as dry season and frequent fires in the winter.